2021
DOI: 10.1038/s41598-021-81113-x
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miR-494-3p attenuates gene HtrA3 transcription to increase inflammatory response in hypoxia/reoxygenation HK2 Cells

Abstract: The occurrence of cardiac surgery-associated acute kidney injury (CSA-AKI) increases hospital stay and mortality. MicroRNAs has a crucial role in AKI. This objective of the current study is to explore the function of hsa-miR-494-3p in inflammatory response in human kidney tubular epithelial (HK2) cells with hypoxia/reoxygenation. According to KDIGO standard, patients after cardiac surgery with cardiopulmonary bypass were divided into two groups: AKI (n = 10) and non-AKI patients (n = 8). HK2 were raised in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…miR-494 refers to a tumor suppressor inhibiting the proliferation and colony formation of tumor cells [ 30 ]. miR-494 can reduce autophagy and apoptosis of PC-12 cells induced by LPS by targeting IL-13 in vitro [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-494 refers to a tumor suppressor inhibiting the proliferation and colony formation of tumor cells [ 30 ]. miR-494 can reduce autophagy and apoptosis of PC-12 cells induced by LPS by targeting IL-13 in vitro [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…As manifested in previous studies, exposure to particles resulted in lung injury and fibrogenesis by modulating miR-494-3p, miR-21, and miR-96 [ 73 75 ]. Of note, miR-494-3p has been known to mediate multi-disease processes, as manifested by enhancing inflammatory response [ 76 ], increasing cell proliferation and migration [ 77 ], and cellular senescence [ 78 ]. Moreover, EVs derived from lung fibroblasts from patients with pulmonary fibrosis were rich in miR-494-3p, which could accelerate epithelial phenotypic changes [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 27 , 28 , 29 , 30 In addition, a study reported that HtrA3 suppressed the hypoxia-reoxygenation-induced inflammation response. 31 However, whether HtrA3 can induce renal cell apoptosis has not been discovered yet during ischemic injury. The results demonstrated that the deletion of HtrA3 attenuated BUMPT and HK-2 cell apoptosis during ATP-depletion injury ( Figure 8 ), thereby supporting its pro-apoptotic role.…”
Section: Discussionmentioning
confidence: 99%